Disciplinarity at the fin de siècle - Anderson, Amanda, 1960-; Valente, Joseph (Princeton University Press, 2002)
Contemporary celebrations of interdisciplinary scholarship in the humanities and social sciences often harbor a distrust of traditional disciplines, which are seen as at best narrow and unimaginative, and at worst complicit in larger forms of power and policing. Disciplinarity at the Fin de Siècle questions these assumptions by examining, for the first time, in so sustained a manner, the rise of a select number of academic disciplines in a historical perspective. This collection of twelve essays focuses on the late Victorian era in Great Britain but also on Germany, France, and America in the same formative period. The contributors - James Buzard, Lauren M. E. Goodlad, Liah Greenfeld, John Guillory, Simon Joyce, Henrika Kuklick, Christopher Lane, Jeff Nunokawa, Arkady Plotnitsky, Ivan Strenski, Athena Vrettos, and Gauri Viswanathan - examine the genealogy of various fields including English, sociology, economics, psychology, and quantum physics. Together with the editors' cogent introduction, they challenge the story of disciplinary formation as solely one of consolidation, constraint, and ideological justification. Addressing a broad range of issues - disciplinary formations, disciplinarity and professionalism, disciplines of the self, discipline and the state, and current disciplinary debates - the book aims to dislodge what the editors call the "comfortable pessimism" that too readily assimilates disciplines to techniques of management or control. It advances considerably the effort to more fully comprehend the complex legacy of the human sciences.